The Negotiation Of Sexual Relationships Among School Pupils In South-Western Uganda - Nyanzi, S.; Pool, R.; Kinsman, J. (AIDS care, 2001)
The objective of the study was to explore how school-going adolescents in south-western Uganda negotiate sexual relationships. Qualitative data were obtained from 15 boys and 15 girls (14-18 years old), during a series of role plays, focus group discussions and one-to-one interviews. A questionnaire was administered to 80 pupils (12-20 years old) from the same school. Most of the pupils were sexually active. Sexual relationships between boys and girls were mediated by peers. Boys initiated relationships. Exchange played an important role in the negotiation of sexual relationships. Money or gifts were given and received in exchange for sexual favours and to strengthen the relationship. To maximize gains, some adolescents had sexual relationships with adults. Sexual relationships were characterized by ambiguity. Love is intertwined with sexual desire, money and prestige. Girls have to be explicit enough to get a good deal; if they are too explicit they will be stigmatized as 'loose' but if they are not interested in money they may be suspected of wanting to spread HIV. Boys try to persuade girls that they have money, but do not want to emphasize this too much. In sexual negotiations a boy must persuade a girl that although he is modern and sophisticated (i.e. experienced) he does not chase after every girl; the girl does not want to come over as an unsophisticated virgin, but does not want to give the impression that she is loose either. There is a tension between the traditional ideal of female chastity and submissiveness and the modern image of sexual freedom. Multiple partnerships were highly valued as a sign of sophistication. Condoms were not considered important. Interventions aimed at reducing the spread of HIV do not seem to be having an effect on the behaviour of this group of adolescents. On the contrary, risky attitudes and behaviour are part of an adolescent ideal of modernity and sophistication. New approaches are needed to persuade this group of the need for change. Shifting the source of interventions from adults to the adolescents themselves, encouraging girls to try other means of earning money and debunking the idea that having many partners is sophisticated may be productive alternatives.